Perencanaan Kolam Retensi di Perumahan Dalam Upaya Penerapan Konsep Drainase Berwawasan Lingkungan - Wardhani, Eka; Kurnia, Indrianti; Irmansyah, Athaya Zahrani (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Cirebon Regency is experiencing flood and drought problems where this area is experiencing a change in land use from green areas to housing due to population growth. This change causes a decrease in the land's ability to absorb water and an increase in water runoff. This research aims to analyze the application of environmentally friendly drainage with retention ponds to overcome this problem. The case study was conducted in a new housing complex with an area of 49.2 ha. The design method of the retention pond is related to the Directorate General of Human Settlements. The results of the research at the site required three retention ponds with a volume of 3,543.60 m3, 4,443.30 m3 and 2,303.40 m3. The efficiencies of reducing runoff water for each pond are 32%, 37%, and 21%. The total reduction efficiency of the three ponds is 90%. The remaining 10% of the runoff water goes into the drainage canal. If you want to implement zero waste, the remaining runoff water can be captured by building absorption wells at several points. The application of this environmentally friendly drainage concept has the effect of reducing runoff water and increasing infiltration water.